2017
DOI: 10.3906/sag-1701-160
|View full text |Cite
|
Sign up to set email alerts
|

Superiorly based nasolabial island flap for reconstruction of the lateral lower eyelid

Abstract: IntroductionReconstruction of the eyelids is a challenging task for plastic and reconstructive surgeons and is mostly performed due to trauma, tumor resection, or, less commonly, congenital abnormalities (e.g., coloboma, Tessier no. 3-6 clefts) (1,2). The decision as to the most appropriate reconstructive option depends on assessment of the eyelid defect in terms of its size, extent, orientation, and, most importantly, location. A method of classifying periocular defects according to location was developed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Studies have shown that there is immune activation in patients with depression. Thymus and spleen are two important immune organs in the body (Wan et al, 2017, Tong, 2014, Naveed et al, 2018, Babenko et al, 2017, Pati et al, 2017, Tatar et al, 2017, Peng et al, 2017, Gao et al, 2017). The pathological changes of spleen and thymus in chronic stress depression rats can be improved significantly after intervention, indicating that it can alleviate the pathological development of depression by interfering with the immune system.…”
Section: Discussmentioning
confidence: 99%
“…Studies have shown that there is immune activation in patients with depression. Thymus and spleen are two important immune organs in the body (Wan et al, 2017, Tong, 2014, Naveed et al, 2018, Babenko et al, 2017, Pati et al, 2017, Tatar et al, 2017, Peng et al, 2017, Gao et al, 2017). The pathological changes of spleen and thymus in chronic stress depression rats can be improved significantly after intervention, indicating that it can alleviate the pathological development of depression by interfering with the immune system.…”
Section: Discussmentioning
confidence: 99%
“…2 As a problematic complication in lower eyelid surgery, ectropion is defined as the inappropriate position of eyelids wherein the lower eyelid margin shows emerges from the globe. 1 Ectropion occurs due to excessive incision of eyelid tissue during blepharoplasty and eyelid reconstruction. 3 In addition, other factors causing ectropion include involutional laxity of the lower eyelid as well as mechanical factors such as bulkiness of the facial flaps in comparison to the adjacent anatomic structures, which results in considerable Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Eyelid reconstructions can be considered as the most challenging surgical procedure and are mostly done due to trauma, tumor resections, and congenital defects. 1 Optimization of aesthetic and functional outcomes is a general goal in the reconstruction of eyelid defects. Overall, eyelid reconstruction must follow basic principles so that the surgeon should use conventional methods for reconstruction before thinking about more complex methods.…”
mentioning
confidence: 99%
See 2 more Smart Citations